The COLTRIMS Reaction Microscope—The Spyhole into the Ultrafast Entangled Dynamics of Atomic and Molecular Systems - Schmidt-Böcking, Horst; Ullrich, Joachim; Dörner, Reinhard; Cocke, Charles Lewis (My University, 2021)
The COLTRIMS Reaction Microscope C-REMI can image the momentum vectors of all emitted charged fragments in an atomic or molecular reactions similar to the bubble chamber in high energy particle physics. C-REMI can detect fragments with “zero” kinetic energy in an ultrahigh vacuum environment by projecting them with weak electromagnetic fields onto position-sensitive detectors. Geometrically a nearly 4π collection solid angle and a nearly 50% efficiency for a fivefold multi-coincidence can be achieved. Measuring time-of-flight and detector position the momenta of the fragments can be measured with excellent resolution (<0.01 a.u.; see A1 in the Appendix). Thus, multivector correlations in momentum space are measured, which provide insight into the entangled dynamics of atomic and molecular quantum systems. From these vector-correlations phases and energies can be deduced which allow for relative time measurements even in the zeptosecond range. C-REMI provides a “spyhole” into the secrets of ultrafast dynamics of atomic and molecular processes. It is applied today around the globe in numerous research projects in physics and chemistry. The purpose for writing this article is to demonstrate the universal application possibilities of C-REMI, and its high multi-coincidence efficiency and high momentum resolution. This paper will not give a review on all milestone experiments performed with C-REMI.